Agricultural Supply Chain Efficiency Measurement using Optimization Equation - Uma Shankar Singh; Osman Sahin (International Journal of Supply Chain Management, 2019)
The study is descriptive but quantitative data collected through the administered structured questionnaire interpreted and presented exploratory with explanations for the primary understanding. The need for finding the relationship and to get the understanding of effect of producer’s variable with vertically coordinated agricultural supply chain variables that can measure the efficiency of agricultural supply chain and can develop the optimized equation is the main idea behind the study. Objectives formulated as to find the relationship of Producer’s variables with agricultural supply chain variables, to understand the effect of Producer’s variables with agricultural supply chain variables and to get the econometric model as the solution for the proposed conceptual model. Cluster sampling method of probability sampling was used to select the respondent from a cluster of green agricultural growers. The sample size for the farmer was 757. Study concludes that, Market and selling, Credit and stock strategy, and prices and transaction cost are having strong relationship and impact on vertically coordinated agricultural supply chain. Constraints in the specific case of producers is conceptually not accepted based on the responses of farmers.